The body snatchers - Smart, Kee nall (Australia : BBC Bristol [production company] ; Sydney : Educational and Training Department [distributor], 1987)
Wildlife on one series
Editor, Peter Simkins ; photography, Stephen Bolwell, Brrie Britton ; music, Startled Inseets
Narrator: David Attenborough
Keywords: Vertebrates